Determinación de la fatiga visual y su relación con el tele estudio, en estudiantes de la carrera de Agroindustria - Huilcapi Carrillo, Iván Alexander (2024)
The present research work was carried outto determine the consequences on visual health of the excessive use of PVD concerning tele-study in the students of the Agroindustry career 2022 –2S of the National University of Chimborazo through the Computer Vision Symptom Scale (CVSS 17) test, to identify the symptoms of users who suffer from Computer Vision Syndrome (SVI). The level of reliability of the test was determined by applying Cronbach's Alpha and KMO coefficients, respectively. Positive results of 0.693 and 0.916 corresponding to each one were obtained. The inductive and analytical methods were used, with a field study for research, comparison, and analysis of the variables in relation to the time of exposure to PVD; in addition, the survey was implemented to the study group to collect information, determining the presence of discomfort related to computer use. After the research, the correlation between the hours of computer use and the consequences that this represented could be observed through the application of Cramer's V measure, with alarge percentage of asymptomatic students using the computer for more than 4 hours a day, but they present discomfort and symptoms, due to the influence of other factors. Based on these results, the following proposal is presented to mitigate the effects of excessive use of PVD; it is necessary to raise awareness about correct visual hygiene, in addition to guaranteeing adequate ergonomic conditions, but above all, implement the 20 -20 -20 rule; in this way, this syndrome can be prevented from reaching its highest peak